Ecotoxicological effects of heavy metals on marine mammals:A systematic review - Malca-Valdez, Joyce Alessandra (2025)
Heavy metal pollution originates from mining, agricultural,and domestic activities, significantly impacting waterresources. It has been reported that between 75% and96% of the world’s seas are contaminated, exposing marinemammals to ecotoxicological effects, with about 60%affected. The data sources used for this research include Scopus, ScienceDirect, Springer, ResearchGate, and the Journalof Wildlife Diseases. Additionally, the PRISMA methodology wasemployed for a systematic review, analyzing 60 articles. The resultsindicate that most studies are from the United States, with theDelphinidae family being the most frequently studied. Furthermore,93% of the studies focus on chronic effects related to bioaccumulationin the liver and kidneys. There is a positive correlation betweenexposure time and concentration differences according to divingdepth. High concentrations of arsenic have been shown to weakenthe immune system, making animals more susceptible to infectiousdiseases, while high levels of cadmium can cause chronic kidneydamage. The remaining 7% of studies address acute effects,revealing that elevated concentrations of mercury and cadmiumare associated with significant damage to cellular organelles and theimmune system. Consequently, heavy metal pollution in marinemammals constitutes a significant problem due to its persistence,bioaccumulation, and biomagnification. These animals, positionedat the top of the food chain, face various exposure pathways, withdietary intake being the most significant.